Contemporary trends and in‐hospital outcomes of mechanical and bioprosthetic surgical aortic valve replacement in the United States. Issue 7 (13th April 2022) - Hiltner, Emily; Erinne, Ikenna; Singh, Anjuli; Chen, Chunguang; Kassotis, John; Russo, Mark; Sethi, Ankur
Abstract: Introduction: The choice between a mechanical versus a bioprosthetic valve in aortic valve replacement (AVR) is based on life expectancy, bleeding risk and comorbidities, since bioprosthetic AVR (bAVR) are associated with a more rapid structural deterioration compared to mechanical AVR (mAVR). The impact of widespread transcatheter valve replacements, on the decision to use bAVR versus mAVR, in the contemporary era and subsequent outcomes remain to be determined. Methods: The National Inpatient database (2009–2018) was used to study trends in admissions for bAVR and mAVR and in‐hospital mortality and outcomes over time. Survey estimation commands were used to determine weighted national estimates. Results: There were 700, 896 ± 18, 285 inpatient visits for AVR with 70.1% (95% CI 69.2%–71.1%) and 29.9% (95% CI 28.9%–30.8%) visits for bAVR and mAVR, respectively. Those undergoing bAVR were significantly older (bAVR [69.8 years] vs. mAVR [62.7 years] p < .001]. The rates of mAVR decreased across all age groups during the study period ( p trend < .001), including patients ≤50 years ( p trend < .001). In‐hospital mortality for mAVR recipients was higher, both after multivariable adjustment (OR 1.35 95% CI 1.26–1.45 p < .001) and propensity matching (mean difference 0.846% ± 0.19%). Conclusion: In the contemporary era, the utilization of mAVR has decreased across all age groups, including those younger than 50 years old. Although mAVR recipients were healthier with less comorbidities, inpatient mortality was higher after mAVR compared to bAVR. In addition to understanding causes for higher in‐hospital mortality after mAVR, future research should focus on developing transcatheter valve replacement friendly bAVR.